2011
DOI: 10.1097/phh.0b013e3181ee9b29
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Communication with Frontline Clinicians During the First Wave of the 2009 Influenza Pandemic

Abstract: Context-During public health emergencies, office-based frontline clinicians are critical partners in the detection, treatment, and control of disease. Communication between public health authorities and frontline clinicians is critical, yet public health agencies, medical societies, and healthcare delivery organizations have all called for improvements.Objectives-Describe communication processes between public health and frontline clinicians during the first wave of the 2009 novel influenza A (H1N1) pandemic; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 13 publications
0
28
1
Order By: Relevance
“…Similar issues were recently documented by a process analysis and survey conducted with primary care providers in Utah following the first wave of the 2009 influenza pandemic. A majority of providers stated that: 1) they received an overwhelming amount of email from public health authorities as well as health care organizations and 2) they desired less frequent, more concise and locally relevant emergency communications during a public health emergency [20]. Despite recognition of these problems, little is known about the potential for HCP alert fatigue from public health communications.…”
Section: Introductionmentioning
confidence: 99%
“…Similar issues were recently documented by a process analysis and survey conducted with primary care providers in Utah following the first wave of the 2009 influenza pandemic. A majority of providers stated that: 1) they received an overwhelming amount of email from public health authorities as well as health care organizations and 2) they desired less frequent, more concise and locally relevant emergency communications during a public health emergency [20]. Despite recognition of these problems, little is known about the potential for HCP alert fatigue from public health communications.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to establishing the RMC, many of the key players who would need to respond to this type of public health events did not know one another. As the H1N1 outbreak evolved, researchers from the center were able to rapidly and systematically evaluate real communication in the field and identify problems with duplication of effort and communication overload (20). After the first wave of the outbreak, a new communication strategy was developed in large part due to the ongoing partnership among the major stakeholders, many of whom were represented in the RMC partnership (Figure 7).…”
Section: Other Impacts Of Partnerships Fostered By Public Health Infomentioning
confidence: 99%
“…Only 54% considered state agency websites their main resource of online investigation of public health data [6]. In another study, Staes et al [7] found that only 35% of clinicians during the 2009 influenza A H1N1 epidemic accessed state agency websites at least once a week while 50% never accessed them at all. In contrast, over half of the participants visited the CDC’s influenza website (53%) at least once a week [7].…”
Section: Introductionmentioning
confidence: 99%